Challenges to establish the diagnosis of aspergillosis in non-laboratory animals: looking for alternatives in veterinary medicine and demonstration of feasibility through two concrete examples in penguins and dolphins - Desoubeaux, Guillaume; Cray, Carolyn; Chesnay, Adélaïde (Frontiers in Cellular and Infection Microbiology, 2022)
Aspergillosis remains difficult to diagnose in animals. Laboratory-based assays are far less developed than those for human medicine, and only few studies have been completed to validate their utility in routine veterinary diagnostics. To overcome the current limitations, veterinarians and researchers have to propose alternative methods including extrapolating from human diagnostic tools and using innovative technology. In the present overview, two specific examples were complementarily addressed in penguins and dolphins to illustrate how is challenging the diagnosis of aspergillosis in animals. Specific focus will be made on the novel application of simple testing in blood based on serological assays or protein electrophoresis and on the new information garnered from metabolomics/proteomics to discover potential new biomarkers. In conclusion, while the diagnostic approach of aspergillosis in veterinary medicine cannot be directly taken from options developed for human medicine, it can certainly serve as inspiration.